(untitled) (Global Journal of Science Frontier Research, 2012)
In this paper, we introduce a Darboux helix to be a curve in 3-space whose Darboux vector makes a constant angle with a fixed straight line. We completely characterize Darboux helices in terms of and thus prove that the class of Darboux helices coincide with the class of slant helices. In special, if we take = constant, the curves are curve of constant precession.